2015
DOI: 10.1039/c5ra08926c
|View full text |Cite
|
Sign up to set email alerts
|

Electroless deposition of Ni3P–Ni arrays on 3-D nickel foam as a high performance anode for lithium-ion batteries

Abstract: We successfully prepared advanced Ni 3 P-Ni array electrodes for Li-ion batteries (LIBs) by electroless deposition on 3-D nickel foam.The array structure of Ni 3 P-Ni can accommodate volume changes during the lithiation/de-lithiation process and promote high-rate capability because the interspaces in such structure can act as ideal volume expansion buffers. It shows excellent electrochemical performance as anode material for LIBs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 33 publications
1
11
1
Order By: Relevance
“…However, the commercial application of MP anodes is hindered by their large volume changes upon Li insertion and extraction that result in particle pulverization and rapid capacity fading [12]. So far, various binary MPs such as MnP4, FePx, CoP3, Cu3P, NiP2, SnP0.94, and Sn4P3 have been fabricated via high-temperature solid-state synthesis, ball milling, solution-phase techniques, and other traditional time-consuming and high-cost stepwise methods [7,9,[12][13][14][15][16][17][18], which often require extreme operating conditions incompatible with practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, the commercial application of MP anodes is hindered by their large volume changes upon Li insertion and extraction that result in particle pulverization and rapid capacity fading [12]. So far, various binary MPs such as MnP4, FePx, CoP3, Cu3P, NiP2, SnP0.94, and Sn4P3 have been fabricated via high-temperature solid-state synthesis, ball milling, solution-phase techniques, and other traditional time-consuming and high-cost stepwise methods [7,9,[12][13][14][15][16][17][18], which often require extreme operating conditions incompatible with practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Such bicontinuous conductive scaffold enables optimization to match the characteristic kinetics of a given battery chemistry. Except for using metal NAAs as current collector (Ti, Cu, Ni, Fe, Co, and Al), the conductive scaffold concept has been applied to many materials by using CNTs as current collector . In both cases, the weight ratio between the current collector and active material needs to be carefully balanced because the energy density of the cell could be largely influenced if the current collector either is electrochemically inactive (e.g., metal or alloy) or has considerably lower ion storage capacity comparing to the active material.…”
Section: Electrochemical Performances Of the Naa Electrodesmentioning
confidence: 99%
“…revealed that the Cu 3 P nanowire anode have the average capacity attenuation drop of only 0.12 % cycle −1 . Therefore, these materials show higher specific capacities and lower capacity attenuation through combining with carbon materials and fabricating nanostructure …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these materials show higher specific capacities and lower capacity attenuation through combining with carbon materials and fabricating nanostructure. [13][14][15][16][17] Recently, mechanical ball milling has been widely applied to synthesis of numerous metal phosphide, such as CoP, [18] SiP 2 , [19] FeP 4 . [20] However, because of high energy consumption, low purity phase and uncontrolled distribution of particles, mechanical ball milling is unable to meet the growing electronics market demand.…”
Section: Introductionmentioning
confidence: 99%